Cyber-security must be a C-suite priority. Issue 2 (February 2017) - Boone, Adam
Abstract : Digital technology has fundamentally changed business practice over the past decade. Cloud-based applications dominate, workers routinely access corporate information remotely via smartphones and access to the corporate network increasingly includes supply chain members, contractors and part time workers. Yet cyber-security has failed to keep up – and some of the responsibility has to lie with the C-suite. Digital technology has fundamentally changed business over the past decade. Yet cyber-security has failed to keep up – and some of the responsibility has to lie with the C-suite. By failing to embrace security expertise and innovation up front, businesses are incurring far too much risk. It is time to address the fragmented, outdated, reactive attitudes to cyber-security that still dominate and make cyber-security a priority for every C-suite, says Adam Boone of Certes Networks.